Analysis of cooling loads and air circulation in the passenger compartment of the CR400AF fast train trailer car - Moch. Sugiri; Parman Sinaga; Andy Fii Aunillah (JTTM : Jurnal Terapan Teknik Mesin, 2024)
The air conditioning system is a system that regulates air circulation and air temperature on the train. The temperature standard for fast train passengers is in accordance with Permen No. 7th year 2022 is 22°C - 26°C. To achieve this temperature, a cooling system is needed that is suitable for the cooling load. This research was conducted on the CR400AF fast train trailer car with the aim of knowing the factors that influence cooling loads, calculating and analyzing cooling loads which are used as a reference in determining air conditioning technical specifications, as well as analyzing air circulation that affects air humidity. The data analysis method used is the quantitative data analysis method. This method is carried out by collecting primary and secondary data to be used as a basis for calculations in answering the problem formulation. Data analysis was carried out by calculating the OTTV (Overall Thermal Transfer Value) according to SNI 03-6389-2000, calculating the cooling load using the CLTD (Cooling Load Temperature Difference) method according to SNI 03-6572-2001, and carrying out an air circulation test referring to Permen No. . 7 of 2022. From the results of the analysis and calculations, the OTTV value is 15.6 Watt/m2. Room eligibility standards according to SNI 03-6389-2000 standards are OTTV values not greater than 45 Watt/m2. The internal cooling load is 15,010 W, the external load and ventilation is 22,688.92 W, the total cooling load is added 10% safety factor of 41.47 kW, the cooling capacity of the AC unit based on technical specifications is 45kW. The average value of air flow velocity during the air circulation test is 0.3 m/s. according to Ministerial Regulation No. 7 of 2022 maximum air circulation speed of 0.5 m/s. From several analysis and calculation results, it can be concluded that the passenger space of the CR400AF fast train trailer car is standard and feasible to operate